An extraordinary form of the Melkersson-Rosenthal syndrome successfully treated with the tumour necrosis factor-α blocker adalimumab. (14th May 2014) - Stein, Juergen; Paulke, Alexander; Schacher, Beate; Noehte, Matthias
Abstract : Melkersson-Rosenthal syndrome (MRS) is a rare granulomatous inflammatory disease characterised by the triad of orofacial oedema, facial nerve palsy and furrowed tongue. We describe the case of a 29-year-old patient suffering from an oligosymptomatic form of the disease with orofacial oedema, cobblestone pattern on the buccal mucosa and swelling of the tongue, accompanied by intermittent fatigue, influenza-like symptoms, intermittent tinnitus and acute hearing loss. An increase of several autoimmune-associated antibodies was also detected. Treatment with prednisolone, azathioprine or methotrexate failed to adequately control all symptoms in the long term. In the absence of a specific and well-established therapy for MRS, treatment with adalimumab was administered. Under adalimumab, total remission of all symptoms was achieved, indicating that tumour necrosis factor-α blockers are a promising therapeutic option for patients with Melkersson-Rosenthal syndrome.